Role of DOTATATE‐PET/CT in preoperative assessment of phaeochromocytoma and paragangliomas. (24th May 2018) - Gild, Matti L.; Naik, Nikita; Hoang, Jeremy; Hsiao, Edward; McGrath, Rachel T.; Sywak, Mark; Sidhu, Stan; Delbridge, Leigh Walter; Robinson, Bruce Gregory; Schembri, Geoff; Clifton‐Bligh, Roderick John
Summary: Context: Diagnosis of paragangliomas (PGL) and phaeochromocytomas (PC) can be challenging particularly if the tumour is small. Detection of metastatic disease is important for comprehensive management of malignant PC/PGL. Somatostatin receptor imaging (SRI) agents have high sensitivity for these tumours, particularly the DOTA family of radiopharmaceuticals labelled with 68 Gallium. Objective: To describe the utility of SRI in primary assessment (ie before surgery) for PC/PGL and whether measures of maximum standardized uptake (SUVmax) could be used to distinguish between adrenal adenomas and PCs. Design: Retrospective analysis of patients with PC and PGL between 2012 and 2017. Patients: Somatostatin receptor imaging (SRI) was performed for suspected PC (n = 46) or PGL (n = 27) of which 36 were during primary assessment and 37 during secondary assessment (follow‐up after surgery). For comparison of adrenal SUVmax, scans from 30 patients without suspected PC/PGL (20 with normal adrenals; 10 with incidental adenomas) were evaluated. Measurements: Baseline description, sensitivity, specificity, Youden's index. Results: Sensitivity of DOTATATE‐PET was 88% for PC and 100% for PGL. False‐negative scans were seen in 2/10 PCs < 28 mm and in 1/14 PCs > 28 mm which had features of cystic degeneration. SUVmax of PCs and PGLs was more than double compared to adrenal adenomas ( P  > .001). Conclusion: Somatostatin receptor imaging (SRI) has high sensitivity in primary assessment for PC and PGL. We recommend that SRI should be performed as part of primary assessment in all suspected PGLs (due to higher risk of multifocal lesions) and in PCs suspected to be associated with hereditary syndromes or metastases.